(untitled) (Research, Society and Development, 2022)
This article aims to analyze the socio-environmental structure of the Nossa Senhora do Livramento Community, located in the Tupé Sustainable Development Reserve (RDS Tupé), with a view to collecting data that characterize the ways of life of the inhabitants of that locality, seeking, next, the indicators for a delineation of the levels related to the minimum living floor to guarantee the survival of the community, especially with regard to health, education, security, economic activity and basic sanitation, among other factors. Conservation units consist of territorial spaces and their environmental resources, including jurisdictional waters, with relevant natural characteristics, with conservation objectives and defined limits, under the special administration regime, to which adequate protection guarantees apply. As for the methodology, it is an applied research, in terms of objectives, exploratory and descriptive, with a qualitative and quantitative approach, based on the case study method, carried out in the Nossa Senhora do Livramento Community, Tupé Sustainable Development Reserve. Therefore, it is expected with this work, to contribute to the knowledge and reflection about the researched elements, which are the territorial space, the human being, the environmental perception and the rights, in an interactive vision, which may matter in the search for solutions for the possible controversies presented through the conclusions obtained.